AMPK: An energy sensor for non-small cell lung cancer progression and treatment - Zhi-Ting Zhong; Xu-Yan Wang; Ying Pan; Ke Zhou; Jing-Hui Chen; Yu-Qi Gao; Bo Dai; Zhi-Ling Zhou; Rui-Qi Wang (Pharmacological Research)
Lung cancer (LC) is the leading cause of cancer-related morbidity and mortality in China, with non-small cell lung cancer (NSCLC) accounting for 85 % of the overall lung cancer cases. AMP-activated protein kinase (AMPK) is a key regulator of energy balance and homeostasis, and its dysregulation is a common feature in various malignancies, particularly in NSCLC with mutations in Liver kinase B1 (LKB1). Studies have shown that the AMPK signalling pathway has a dual role in NSCLC progression, both inhibiting and promoting the progression of malignant tumours. Therefore, drugs targeting the AMPK signalling pathway may hold significant promise for therapeutic application in NSCLC. This review aims to examine the manifestations and mechanisms by which AMPK and its associated signalling molecules influence NSCLC progression and treatment. Firstly, we discuss the critical importance of AMPK within the mutational context of NSCLC. Secondly, we summarise the drugs and related substances that modulate the AMPK signalling pathway in NSCLC and evaluate the evidence from preclinical studies on combination AMPK-targeted therapies to address the issue of drug resistance in NSCLC under current clinical treatments. In summary, this paper highlights the critical importance of developing AMPK-targeted drugs to enhance therapeutic efficacy in NSCLC, as well as the potential for applying these drugs in clinical therapy to overcome drug resistance.